2018
DOI: 10.1016/j.agee.2017.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Assessing changes in structural vegetation and soil properties following riparian restoration

Abstract: After the embargo period  via non-commercial hosting platforms such as their institutional repository  via commercial sites with which Elsevier has an agreement In all cases accepted manuscripts should: link to the formal publication via its DOI  bear a CC-BY-NC-ND licensethis is easy to do  if aggregated with other manuscripts, for example in a repository or other site, be shared in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 33 publications
2
19
0
1
Order By: Relevance
“…While we showed that restored (treated) sites had a better riparian vegetation condition score 10 years after restoration compared to untreated sites, the scores recorded were still less than half that of healthy sites (i.e., a RARC score of 43 [37]). The 10 year timeframe appears sufficient for changes in indicators such as width of riparian canopy vegetation and canopy cover to occur, similar to that found by Hale et al [25], after a similar timeframe. The timeframe, however, may be insufficient to result in measurable changes in leaf litter, hollow bearing trees and coarse woody debris which reflect the presence of mature vegetation [47].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…While we showed that restored (treated) sites had a better riparian vegetation condition score 10 years after restoration compared to untreated sites, the scores recorded were still less than half that of healthy sites (i.e., a RARC score of 43 [37]). The 10 year timeframe appears sufficient for changes in indicators such as width of riparian canopy vegetation and canopy cover to occur, similar to that found by Hale et al [25], after a similar timeframe. The timeframe, however, may be insufficient to result in measurable changes in leaf litter, hollow bearing trees and coarse woody debris which reflect the presence of mature vegetation [47].…”
Section: Discussionsupporting
confidence: 83%
“…We were unable to evaluate the outcomes of the restoration for instream sediment and nutrient loads because site scale water quality data were not available. It is likely, however, that the removal of livestock and the observed improvements in riparian vegetation condition have increased the ability of the riparian zone to filter and process nutrients, (see [25,26]) and thus, reduce sediment and nutrient loads in the rivers of the UMRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Riparian soils and vegetation form the foundation of numerous ecosystem services, being important for the overall biodiversity and biogeochemistry of river ecosystems (Hale et al, 2018). Specifically, riparian vegetation can promote ecological balance, biodiversity, and agricultural production by stabilizing stream banks and improving water quality.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation plays an important role in the regulation of soil resource patterns and availability in riparian zones (Hou & Fu, 2014). The occurrence and succession of riparian vegetation are closely related to soils and other environmental factors (Hale et al, 2018;Bruno et al, 2014). For example, riparian vegetation modifies both physical and chemical properties of soils, including nutrient inputs and outputs, soil moisture, particle size, aggregation, sedimentation, and dispersion (Nielsen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%